Personal Branding Content Creator di Media Sosial Tiktok: Studi Kasus pada Akun Tiktok @Ejpeace.ent - Irsyad Maulana Wahyu; Riza Hernawati (Bandung Conference Series: Public Relations, 2024)
Abstract. Currently, social media is growing rapidly, both in terms of quality and quantity. The social media users also consist of various ages from children to adults and also many older people use social media too. For most people, social media is not only for exchanging information or messages but also means of promotion or branding. One of the social media that is currently popular and being used by people is Tiktok. Blekjek is a Content creator Tiktok in the comedy category. The creation of their content, Blekjek has their own Personal branding. The concept of being children is one of the characteristics of their content. The aim for this study was to find out how the concept of being a child becomes their Personal branding. This research was conducted by using qualitative methods with a constructive paradigm and a general case study approach. By using this method, the researcher wanted to find out how the concept of being a child becomes Blekjek's personal brandingon Tiktok social media. The data collection techniques for this research are interviews, observation, and documentation. The informants for this researh were personnel, production team, and followers of Blekjek on Tiktok. The results of this study show the selection of initial content concepts which include the concept of humor, and parody ideas of children, mothers, and blackpink. Next in the content creation process there are eight stages, namely meetings, sharing ideas, selecting, discussing, filming, editing, reviewing, and uploading. Furthermore, in selecting captions, they go through several processes, namely content analysis, word search, collecting captions, determining captions, and uploading. The concept of children is the identity and hallmark of Blekjek. Abstrak. Pada saat ini media sosial semakin berkembang pesat, baik dari segi kualitas maupun kuantitasnya. Penggunanya pun terdiri dari beragam usia mulai dari anak-anak hingga orang dewasa, sekalipun yang sudah lanjut usia banyak yang menggunakan sosial media. Media sosial bagi kebanyakan orang bukan hanya untuk saling bertukar informasi maupun pesan tapi bisa juga sebagai sarana promosi ataupun sarana branding. Salah satu media sosial yang sedang ramai pada saat ini yaitu TikTok. Blekjek yang merupakan salah satu Content creator dengan kategori komedi. Dalam membuat kontennya, Blekjek memiliki Personal branding tersendiri. Konsep menjadi anak-anak adalah salah satu ciri khas dari Content creator tersebut. Penelitian ini bertujuan untuk mengetahui bagaimana konsep menjadi anak-anak membentuk Personal branding mereka. Metode penelitian yang digunakan adalah kualitatif dengan paradigm kontrukvis dan pendekatan studi kasus umum. Dengan menggunakan metode tersebut, peneliti ingin mengetahui bagaimana konsep menjadi anak-anak membentuk personal branding Blekjek dalam media sosial TikTok. Teknik pengumpulan data yang dilakukan adalah wawancara, observasi, dan dokumentasi. Informan yang diambil dalam penelitian ini adalah personil, tim produksi, dan pengikut TikTok Blekjek. Hasil penelitian memperlihatkan pemilihan konsep awal konten yang meliputi konsep humor, dan ide parodi anak-anak, ibu-ibu, dan blackpink. Berikutnya dalam proses pembuatan konten terdapat delapan tahap yaitu rapat, sharing ide, pemilihan, diskusi, syuting, editing, review, dan upload. Selanjutnya, dalam pemilihan caption mereka melalui beberapa proses yaitu analisis konten, pencarian kata, mengumpulkan caption, menentukan caption, dan upload. Konsep anak-anak menjadi identitas dan ciri khas dari Blekjek.